Cyclophosphamide augments the efficacy of in situ vaccination in a mouse melanoma model - Tsarovsky, Noah; Felder, Mildred; Heck, Mackenzie; Slowinski, Jacob; Rasmussen, Kayla; VandenHeuvel, Sabrina; Zaborek, Jen; Morris, Zachary S.; Erbe, Amy K.; Sondel, Paul M.; Rakhmilevich, Alexander L. (Frontiers in Oncology, 2023)
We have previously shown that an intratumoral (IT) injection of the hu14.18-IL2 immunocytokine (IC), an anti-GD2 antibody linked to interleukin 2, can serve as an in situ vaccine and synergize with local radiotherapy (RT) to induce T cell-mediated antitumor effects.We hypothesized that cyclophosphamide (CY), a chemotherapeutic agent capable of depleting T regulatory cells (Tregs), would augment in situ vaccination. GD2 + B78 mouse melanoma cells were injected intradermally in syngeneic C57BL/6 mice. Treatments with RT (12Gy) and/or CY (100 mg/kg i.p.) started when tumors reached 100-300 mm 3 (day 0 of treatment), followed by five daily injections of IT-IC (25 mcg) on days 5-9. Tumor growth and survival were followed.In addition, tumors were analyzed by flow cytometry. Similar to RT, CY enhanced the antitumor effect of IC. The strongest antitumor effect was achieved when CY, RT and IC were combined, as compared to combinations of IC+RT or IC+CY. Flow cytometric analyses showed that the combined treatment with CY, RT and IC decreased Tregs and increased the ratio of CD8+ cells/Tregs within the tumors. Moreover, in mice bearing two separate tumors, the combination of RT and IT-IC delivered to one tumor, together with systemic CY, led to a systemic antitumor effect detected as shrinkage of the tumor not treated directly with RT and IT-IC. Cured mice developed immunological memory as they were able to reject B78 tumor rechallenge. Taken together, these preclinical results show that CY can augment the antitumor efficacy of IT-IC, given alone or in combination with local RT, suggesting potential benefit in clinical testing of these combinations.